2011
DOI: 10.5455/vetworld.2011.550-553
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Inter-relationship among Soil, forage and Dairy cattle in Kashmir, India

Abstract: Samples of soil, forage and blood serum of cattle in six villages Ganderbal district of kashmir were collected and analysed for different macro and micro mineral contents to establish the mineral correlation among soil, forage and animals. The macro and micro mineral contents in soils of Ganderbal district were higher than their respective critical levels except Mn. Similarly, in forage except for zinc all the mineral values were above critical level. The study also revealed the serum mineral values above the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…The mineral content of the honey depends on geographical area, climatic conditions and soil type of the fl oral source. It was reported that soil in Kashmir valley of India did not contain high amount of minerals like Cu, Fe, Zn and Co [Bhat et al, 2011;Yatoo et al, 2011] which might be the reason of low level of mineral content in the studied samples of honey varieties.…”
Section: Mineral Analysismentioning
confidence: 99%
“…The mineral content of the honey depends on geographical area, climatic conditions and soil type of the fl oral source. It was reported that soil in Kashmir valley of India did not contain high amount of minerals like Cu, Fe, Zn and Co [Bhat et al, 2011;Yatoo et al, 2011] which might be the reason of low level of mineral content in the studied samples of honey varieties.…”
Section: Mineral Analysismentioning
confidence: 99%
“…Das et al (2009) also reported a low level of P but comparatively higher value for Ca and Mg in four districts of Tripura. However, contrasting figures were observed by Bhat et al (2011) who reported a high concentration of Ca, P and Mg in different districts of Kashmir, India. Ramana et al (2011) observed that among the cultivated green fodders, the Ca content was marginally deficient in sorghum green (0.19-0.27%), para grass (0.37%), hybrid napier (0.43-0.45%) were moderate in Ca while Lucerne was rich in Ca (1.31%) in Reddy district of Andhra Pradesh.…”
Section: Mineral Content In Foddermentioning
confidence: 82%
“…The nutrition of grazing animals is a complicated interaction of soils, plants, and animals [1,2]. Cattle sometimes deteriorate in spite of an abundant feed supply because mineral requirements depend on the level of productivity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cattle sometimes deteriorate in spite of an abundant feed supply because mineral requirements depend on the level of productivity [3]. Many factors affect mineral requirements, including nature and level of production, age, level and chemical form of elements, interrelationship with other nutrients, mineral intake, breed and animal adaptation [2,3]. Mineral deficiencies in soils and pastures may be responsible for low production and reproductive problems among grazing animals in the tropics.…”
Section: Introductionmentioning
confidence: 99%